A comparative study of multi-material data structures for computational physics applications. (15th July 2019) - Fogerty, Shane; Martineau, Matt; Garimella, Rao; Robey, Robert
Abstract: The data structures used to represent the multi-material state of a computational physics application can have a significant impact on its performance. We look at efficient data structures for applications where there may be many materials overall, but where most computational cells contain only one or a few of these materials. We develop simple performance models for selecting possible data structures and programming patterns. We verify the analytic performance models with a small test program of the representative cases. We discuss the impact of these techniques and analysis for multi-material physics applications, which are also applicable to a wide range of sparse computational data structures.